Rivaroxaban versus low-molecular-weight heparin for venous thromboembolism prophylaxis: a systematic review of efficacy, safety, and cost-effectiveness - Li, Bin; Zhao, Ling (Frontiers in Pharmacology, 2025)
Hospitalization significantly elevates venous thromboembolism (VTE) risk, yet optimal prophylactic anticoagulation remains debated. While low-molecular-weight heparin (LMWH) has long been the standard, direct oral anticoagulants (DOACs) like rivaroxaban offer oral administration without routine monitoring. We systematically reviewed 24 studies identified through PubMed and Web of Science (2010–2024), using predefined inclusion and exclusion criteria. Studies were screened, duplicates removed, and data extracted on efficacy, safety, cost-effectiveness, and patient-centered outcomes. High-risk subgroups, such as those with cancer or renal impairment were a focus of analysis. Efficacy: Rivaroxaban demonstrated non-inferiority to LMWH in VTE prevention, with superior postoperative thromboprophylaxis in orthopedic patients. Safety: Minor bleeding incidence was marginally higher with rivaroxaban, but major bleeding risk was comparable. Economics: Rivaroxaban reduced costs by approximately 1,200 per VTE patient, particularly in cancer-related cases. Rivaroxaban provides equally effective VTE prophylaxis with enhanced practicality (oral administration, no monitoring) and significant healthcare savings. Therapy selection should prioritize renal function, cancer status, and bleeding risk. Future research must address DOAC safety in severe renal/hepatic impairment and optimize reversal-agent accessibility.